Epidemiological Dynamics of Xanthomonas xonopodis pv. phaseoli in French bean (Phaseolus vulgaris): Unraveling the Factors Governing Bacterial Blight Pathogenesis - Suchita, S.; Kansal, S.; Sharma, R.; Parwan, S. (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted during May, 2020 to June, 2021 in the Department of Plant Pathology Laboratory of Dr. Y.S Parmar University of Horticulture and Forestry, Nauni, located in Solan district of Himachal Pradesh, India to study the role of various epidemiological parameters on the development of common bacterial blight of French bean. The diseased samples were collected and the pathogen was isolated and purified on Luria Bertani (LB) agar plates. The pathogenicity test was performed on the potted plants as well as on the detached leaves using carborundum abrasion and pin prick method of inoculation. The incubation period on potted plants using carborundum abrasion and pin prick method revealed the initial symptoms after 117.60 h and 120.30 h, respectively, while on detached leaves they were visible after 72.30 h and 84.50 h of inoculation, respectively. Further to study the effect of different epidemiological factors on disease development, the leaves inoculated using carborundum abrasion were subjected to four temperature levels, five relative humidity levels and five different durations of leaf wetness under controlled conditions in relative humidity cum temperature control cabinet. The observations were recorded at different intervals and the data revealed that the pathogen caused severe symptoms on the leaves with high apparent rate of infection under 30°C temperature, 100% RH and a maximum of 24 h of leaf wetness. It was observed that the severity of disease decreased as the temperature raised from 30°C and increased with the rise in RH levels and leaf wetness duration.